ZFYVE26/SPASTIZIN and SPG11/SPATACSIN mutations in hereditary spastic paraplegia types AR-SPG15 and AR-SPG11 have different effects on autophagy and endocytosis. Issue 1 (2nd January 2019) - Vantaggiato, Chiara; Panzeri, Elena; Castelli, Marianna; Citterio, Andrea; Arnoldi, Alessia; Santorelli, Filippo Maria; Liguori, Rocco; Scarlato, Marina; Musumeci, Olimpia; Toscano, Antonio; Clementi, Emilio; Bassi, Maria Teresa
ABSTRACT: ZFYVE26/Spastizin and SPG11/Spatacsin encode 2 large proteins that are mutated in hereditary autosomal-recessive spastic paraplegia/paraparesis (HSP) type 15 (AR-SPG15) and type 11 (AR-SPG11), respectively. We previously have reported that AR-SPG15-related ZFYVE26 mutations lead to autophagy defects with accumulation of immature autophagosomes. ZFYVE26 and SPG11 were found to be part of a complex including the AP5 (adaptor related protein complex 5) and to have a critical role in autophagic lysosomal reformation with identification of autophagic and lysosomal defects in cells with both AR-SPG15- and AR-SPG11-related mutations. In spite of these similarities between the 2 proteins, here we report that ZFYVE26 and SPG11 are differently involved in autophagy and endocytosis. We found that both ZFYVE26 and SPG11 interact with RAB5A and RAB11, 2 proteins regulating endosome trafficking and maturation, but only ZFYVE26 mutations affected RAB protein interactions and activation. ZFYVE26 mutations lead to defects in the fusion between autophagosomes and endosomes, while SPG11 mutations do not affect this step and lead to a milder autophagy defect. We thus demonstrate that ZFYVE26 and SPG11 affect the same cellular physiological processes, albeit at different levels: both proteins have a role in autophagic lysosome reformation, but only ZFYVE26 acts at the intersection between endocytosis and autophagy, thus representing a key player in these 2 processes. Indeed expression of the constitutively active form of RAB5A in cells with AR-SPG15-related mutations partially rescues the autophagy defect. Finally the model we propose demonstrates that autophagy and the endolysosomal pathway are central processes in the pathogenesis of these complicated forms of hereditary spastic paraparesis. Abbreviations : ALR, autophagic lysosome reformation; AP5, adaptor related protein complex 5; AR, autosomal-recessive; HSP, hereditary spastic paraplegia/paraparesis; ATG14, autophagy related 14; BafA, bafilomycin A1 ; BECN1, beclin 1; EBSS, Earle balanced salt solution; EEA1, early endosome antigen 1; EGF, epidermal growth factor; EGFR, epidermal growth factor receptor; GDP, guanosine diphosphate; GFP, green fluorescent protein; GTP, guanosine triphosphate; HSP, hereditary spastic paraplegias; LBPA, lysobisphosphatidic acid; MAP1LC3B/LC3B, microtubule associated protein 1 light chain 3 beta; MVBs, multivesicular bodies; PIK3C3, phosphatidylinositol 3-kinase, catalytic subunit type 3; PIK3R4, phosphoinositide-3-kinase regulatory subunit 4; PtdIns3P, phosphatidylinositol-3-phosphate; RFP, red fluorescent protein; RUBCN, RUN and cysteine rich domain containing beclin 1 interacting protein; shRNA, short hairpin RNA; SQSTM1/p62, sequestosome 1; TCC: thin corpus callosum; TF, transferrin; UVRAG, UV radiation resistance associated.